Naven or the Other Self : A Relational Approach to Ritual Action - Houseman, Michael. (Numen Book Series, 1998)
In this work, the author propose a novel theory of ritual action founded upon an in-depth study of the wide variety of behaviors that the Iatmul of Papua New Guinea identify as naven: a transvestism rite studied by Gregory Bateson in the 1930s and documented by other anthropologists since. Ritual performance is shown to involve the construction of complex relational networks entailing the condensation of contradictory modes of relationship in accordance with over-arching interactive forms. In this volume, inquiry into the history of anthropology, detailed ethnographic analysis and theoretical discussion are combined. The first part examines Bateson's and others' understandings of naven; the second offers a reinterpretation of this ritual in the light of new ethnographic data; and the third proposes a general approach to the analysis of ritual and suggests how this perspective may be applied elsewhere.